International geophysical year (1957-1958) and geophysics of Vietnam for period 1957-1968 - Luu, Le Van (Vietnam Journal of Marine Science and Technology, 2017)
During the “International Geophysical Year 1957-1958”, the Vietnam National Committee of International Geophysical Year had been established. In 1957, the Polish Academy of Sciences supported equipment and helped to establish the geophysical observatories in Sapa, Lao Cai and Phu Lien, Hai Phong, Vietnam. At these stations, measurements on geomagnetics, atmosphere, atmospheric physics, atmospheric radioactive contamination, and seismics, etc. have been being operated. From 1960s to now, many research results using observed data at these stations have been published in Poland and Vietnam.